2018
DOI: 10.1111/cdoe.12381
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, migration status and dental caries experience among adults in East London

Abstract: Large inequalities in caries experience were found between foreign- and UK-born adults, with considerable variation across ethnic groups. Looking beyond cultural explanations, in favour of social and environmental factors, may help to explain those inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Japanese national health data showed that lower educational attainment and lower equivalent household expenditure were associated with fewer remaining teeth [ 27 ], while lower income was associated with poor dental status in Japanese older people [ 28 ]. Similarly, socioeconomic inequalities, number of remaining teeth [ 29 ], edentulism [ 30 ], dental caries [ 31 , 32 ] and periodontal disease [ 33 , 34 ] were reported in the UK. Using large cohort data with harmonised measures, our findings of oral health inequalities determined by income and education offer extended support to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Japanese national health data showed that lower educational attainment and lower equivalent household expenditure were associated with fewer remaining teeth [ 27 ], while lower income was associated with poor dental status in Japanese older people [ 28 ]. Similarly, socioeconomic inequalities, number of remaining teeth [ 29 ], edentulism [ 30 ], dental caries [ 31 , 32 ] and periodontal disease [ 33 , 34 ] were reported in the UK. Using large cohort data with harmonised measures, our findings of oral health inequalities determined by income and education offer extended support to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These six articles included a critical review of income and oral health, which called for an intersectionality approach in its conclusion 33 . A further two papers mentioned intersectionality only in the discussion sections 34,35 . Wright presented a conference paper on intersectionality, oral health and tobacco use focusing on Black people in the United States 36 .…”
Section: What Do We Know About the Application Of Intersectionality Imentioning
confidence: 99%
“…For example, a study by Schwartz et al 6 on oral health inequalities associated with sexual orientation (divided as Gay/Lesbian, Bisexual, exclusively Heterosexual and “Homosexually experienced”) misses an opportunity to understand the complexity of how sexual orientation intersects with gender, race and ethnicity, income, and education to produce oral health problems. Similarly, while Delgado‐Angulo et al 34 used intersectionality theory to explore the association between ethnicity and immigration status and caries, in using adjusted regression models to identity independent effects and dominant identities, they applied a multiplicative approach 41 . In so doing, they ignore gender and miss the opportunity to understand how inequalities are experienced by different intersections (eg being a male, White, newly arrived immigrant in the UK subjected to discrimination).…”
Section: What Do We Know About the Application Of Intersectionality Imentioning
confidence: 99%
“…These patients will seek help in an ED when suffering from an acute problem, as costs will then be covered by the compulsory health insurance. Especially immigrants from different cultural backgrounds are not familiar with preventive care services, such as routine screening, which can detect early oral health problems before they become symptomatic, expensive, and potentially damaging [27][28][29][30][31]. The key problem is that EDs are normally not equipped to provide definitive dental care.…”
Section: Oral Health Of Immigrantsmentioning
confidence: 99%
“…Those affected cannot obtain adequate information about where to seek help. These factors may result in the inappropriate usage of emergency services [25,29].…”
Section: Oral Health Of Immigrantsmentioning
confidence: 99%